2015
DOI: 10.1037/adb0000107
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in facilitator and client behavior during group motivational interviewing sessions.

Abstract: There is considerable evidence for Motivational interviewing (MI) in changing problematic behaviors. Research on the causal chain for MI suggests influence of facilitator speech on client speech. This association has been examined using macro (session-level) and micro (utterance-level) measures; however, effects across sessions have largely been unexplored, particularly with groups. We evaluated a sample of 129 adolescent group MI sessions, using a behavioral coding system and timing information to generate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The effectiveness of open questions on eliciting change language throughout the session could also be examined. For example, one study found that open questions suppressed CT at the beginning of a group MI sessions, but enhanced CT at the end of the session (Houck et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of open questions on eliciting change language throughout the session could also be examined. For example, one study found that open questions suppressed CT at the beginning of a group MI sessions, but enhanced CT at the end of the session (Houck et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction effects were probed using simple slopes analysis, using procedures described by Preacher and colleagues (Preacher, Curran, & Bauer, 2006). Finally, to examine the effects of feedback on therapist MI skill, within the NF group we split each CACTI file at the time of the first NF utterance using procedures developed by the second author (Houck, Hunter, Benson, Cochrum, & Rowell, 2015) and computed behavior counts and summary scores separately for each segment. MI skill was evaluated using standard summary measures including the number of MI-consistent (MICO) and MI-inconsistent behaviors (MIIN), each scaled as described above, as well as the percentage of MI-consistent utterances (%MIC; i.e., MICO/(MICO + MIIN)).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, CT utterances were associated with significant decreases in past 30 day alcohol use, heavy drinking in the past 30 days, and intentions to use alcohol three months later (D'Amico et al, 2015). Two other studies from this same sample of youth highlighted the importance of facilitator speech for increasing CT at the beginning and end of the group session (Houck et al, 2015), and showed that particular subtypes of CT in the group setting, such as reasons (e.g., I should cut back on my use because my grades are dropping) and commitment (e.g., I stopped seeing him so I wouldn’t smoke), were strongly related to improved AOD outcomes for group members (Osilla et al, 2015). Finally, a 2016 study described a new coding scheme to assess adolescent verbal behavior during group sessions for high school students, finding that it was possible to assess language at the group level when coding live, while the group was occurring.…”
mentioning
confidence: 92%
“…There are only five published studies to date (D'Amico et al, 2015; Engle et al, 2010; Houck et al, 2015; Ladd, Tomlinson, Myers, & Anderson, 2016; Osilla et al, 2015) that have analyzed the group process by coding the speech that occurs during the group and examining how this speech relates to behavior change. Four of these studies were conducted with at-risk youth; however, none of them examined how speech during the group may affect both AOD behavior and risky sexual behavior.…”
mentioning
confidence: 99%